Analisis Kemampuan Berpikir Kreatif Siswa Kelas X dalam Memecahkan Masalah Matematika Materi Trigonometri - Fauzia, Muhlisa Nurul; Ahmad Farham Majid (Department of Mathematics Education, 2024)
This study aims to describe the creative thinking abilities of class X students of SMA Negeri 4 Bulukumba in the aspects of fluency, flexibility, originality, and elaboration in solving mathematical problems on Trigonometry material. This study is descriptive qualitative. The subjects of the study were class X.1 students in the 2023/2024 academic year. Data were collected through tests, interviews, and documentation, then validated using technical triangulation. The results of the study showed that in the fluency aspect, high-level subjects were able to solve problems fluently and correctly, while medium-level subjects were able to identify what was known and asked in the question even though there were errors and the low category had not been able to solve it well. In the flexibility aspect, high-level subjects were able to use more than one way to solve the problem, while the medium category subjects were only able to solve one problem using more than one different method well and low were only able to do it in one way. In the originality aspect, high-level subjects were able to solve problems in an unusual way, while medium category subjects were able to solve them in an unusual way but there were errors in the solution process and low were not able to solve them well. In the elaboration aspect, high-level subjects are able to solve problems in a structured and detailed sequence, while subjects in the medium category are able to solve problems by writing down the solution steps in detail but there are still errors in their calculations and the low category is not yet able to solve them well.